Role of Platelet-Derived Tgfβ1 in the Progression of Ovarian Cancer - Hu, Qianghua; Hisamatsu, Takeshi; Haemmerle, Monika; Cho, Min Soon; Pradeep, Sunila; Rupaimoole, Rajesha; Rodriguez-Aguayo, Cristian; Lopez-Berestein, Gabriel; Wong, Stephen T C; Sood, Anil K; Afshar-Kharghan, Vahid (Clinical cancer research, 2017)
Transforming growth factor β1 (Tgfβ1) plays an important role in cancer. Most of Tgfβ1 in plasma is from platelets; thus, we studied whether platelet Tgfβ1 has any role in the progression of ovarian cancer, and whether this role is limited to metastasis or also involves the growth of primary tumors. We compared the growth of murine ovarian cancer cell-induced tumors in platelet-specific Tgfβ1-deficient mice and wild-type mice. Using resected tumor nodules, we studied the effect of platelet Tgfβ1 on neoangiogenesis and on platelet extravasation into tumors. To investigate the effect of Tgfβ1 at different stages of ovarian cancer, we reduced expression of Tgfβ1 receptor (its TgfβR1 component) in tumors at different time points after injection of cancer cells, and compared the final tumor size. Lack of platelet Tgfβ1 in mice reduced tumor growth, neoangiogenesis, and platelet extravasation. Ovarian cancer tumors in platelet-specific Tgfβ1-deficient mice reached less than half of their size in wild-type littermates. Knockdown of TgfβR1 on cancer cells in the first 2 weeks after their injection reduced tumor growth, but was less effective if initiated after 3 weeks. We showed that platelet Tgfβ1 increased the growth of primary tumors in murine models of ovarian cancer. We also showed that inhibition of TgfβR1 is more effective in reducing the growth of ovarian cancer if initiated earlier. Our results supported a therapeutic benefit in preventing platelet activation, degranulation, and release of Tgfβ1 in ovarian cancer. .